2023
DOI: 10.1002/jms.4903
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bibenzyls and evaluation of imitative wild planting techniques in Dendrobium officinale by HPLC‐ESI‐MSn

Abstract: Dendrobium officinale is a traditional Chinese herb with beneficial properties. Modern pharmacological studies show that bibenzyl is one of the antitumor active ingredients, but there is no effective quality control method for identifying ingredients. In this study, the composition of bibenzyls in Dendrobium officinale was studied by high‐performance liquid chromatography coupled with electrospray ionization multistage mass spectrometry (HPLC‐ESI‐MSn). A total of nine isolated bibenzyls and their glycosides, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The characteristic chromatograms of all samples were shown in S1C and S1D Fig . Peaks L1~6 were determined to be lignans and peaks B1~5 were identified as bibenzyls based on their UV spectra [ 37 ]. Both compounds have maximum absorption at 215 and 270 in the UV spectrum, but the difference is that the UV spectrum of bibenzyl compounds has a higher shoulder peak at the maximum absorption of 215 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic chromatograms of all samples were shown in S1C and S1D Fig . Peaks L1~6 were determined to be lignans and peaks B1~5 were identified as bibenzyls based on their UV spectra [ 37 ]. Both compounds have maximum absorption at 215 and 270 in the UV spectrum, but the difference is that the UV spectrum of bibenzyl compounds has a higher shoulder peak at the maximum absorption of 215 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al revealed that D. officinale supplementation can promote alcohol metabolism and alleviate alcoholic fatty liver disease [5]. An increasing body of studies has demonstrated that a variety of active compounds, including polysaccharides, flavonoids, mannitol, naringenin, and total saponins, are closely associated with the antioxidant, anti-cancer, and anti-inflammatory properties of D. officinale [6][7][8]. Due to its health benefits and therapeutic properties, D. officinale has been widely prepared into a variety of health products, such as oral liquid, lozenges, capsules, and so on.…”
Section: Introductionmentioning
confidence: 99%